EXPLORING THE IMPACT OF VIRTUAL CHANGING ROOM ON CONSUMER BEHAVIOR IN THE ONLINE RETAIL INDUSTRY - Syed Hasnain Abbas; Yawar Arshad; Sohaib Uz Zaman (International Journal of Contemporary Issues in Social Sciences, 2024)
E-commerce boasts significant advantages over traditional shopping in terms of time, choice, and cost-effectiveness, but it falls short in providing a holistic shopping experience. A major drawback of online shopping is the lack of physical sensation or tactile engagement. To address this, some businesses are now integrating Virtual Fitting Rooms (VFRs) on their websites to simulate a more realistic buying experience. This research aims to explore how the introduction of an online VFR impacts consumers’ browsing behavior and purchase intent across both online and offline shopping environments. Virtual changing rooms serve as a technological innovation designed to minimize the disparity between conventional in-store shopping experiences and the convenience of online purchases. The research focuses on several dimensions of this influence, encompassing enhanced customer satisfaction, reduced product returns, personalized marketing facilitated by data collection, heightened consumer confidence in purchases, expanded market reach, and the inherent challenges associated with implementing such technology..The target population in this research was determined by the environment under which the study was carried out, and here all the online consumers were involved in this survey. We use sample size of 100 respondents.As per the R value analysis given there is positive impact of consumer experience on consumer behavior in online retail industry due to virtual changing room.